Influence of age, sex and dental status in mandible radiomorphometric indices of a Venezuelan adult sample - Piña-D’ Abreu, Mónica Silu (2018)
Objective: To evaluate the influence of age, sex and dental status on radio-morphometric indexes of the mandible, obtained from panoramic radiographs of a Venezuelan adults. Methods: The sample consisted of 156 digital panoramic radiographs of individuals of both sexes (78 men and 78 women), with ages between 20 and 81 years old, where the following indexes were measured by ImageJ software: MC=thickness of the mandibular cortex, MRH= mental region height, ARR=degree of alveolar ridge reabsorption, PMI=panoramic mandibular index, AGI=antegonial index, GI=gonial index, MRH=- maximum height of the ramus, GA=gonial angle. Descriptive statistics, Spearman correlations and differences in means were obtained using the Mann-Whitney test. Results: There was a tendency to measurement values reduction for the indices obtained from age groups, for both sexes, as well as statistically significant differences between men and women, with the exception of MC and AGI. When comparing the observed values for the sexes by age groups, significant differences were found in the older age groups (p<0.001). There was a negative correlation between the indexes and the chronological age, being statistically significant in MRH, ARR, PMI, AGI and GI. In both sexes the dentition status showed a positive and significant correlation with ARR. Conclusions: The values of the indexes decreased with age and showed sexual dimorphism, which was evident after 50 years, the dental status was significantly related to the ARR.